Specialised Translation - Rogers, M. author. aut Link
X, 175 p.
Keywords: This book shifts the common perception of specialised or 'LSP' translation as necessarily banal and straightforward towards a more realistic understanding of it as a complex and multilayered phenomenon which belies its standard negative binary definition as 'non-literary'.